2022
DOI: 10.1002/hsr2.606
|View full text |Cite
|
Sign up to set email alerts
|

The role of blood urea nitrogen to serum albumin ratio in the prediction of severity and 30‐day mortality in patients with COVID‐19

Abstract: Background: Considering the role of higher blood urea nitrogen and lower serum albumin (SA) levels in deceased coronavirus disease 2019 patients, an increased blood urea nitrogen to SA (B/A) ratio may help to determine those at higher risk of critical illness. This study aimed to evaluate the correlation of the B/A ratio with severity and 30-day mortality in COVID-19 patients.Methods: A total of 433 adult patients with COVID-19 were enrolled. The laboratory markers were measured on admission. Disease severity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…3). [20][21][22][23][31][32][33] Sensitivity analysis reinforced the robustness of the result by showing no significant impact of the finding from a single study on the overall outcome. Publication bias was not investigated because only 7 studies were available.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…3). [20][21][22][23][31][32][33] Sensitivity analysis reinforced the robustness of the result by showing no significant impact of the finding from a single study on the overall outcome. Publication bias was not investigated because only 7 studies were available.…”
Section: Discussionmentioning
confidence: 96%
“…5). [20][21][22][23]31,33] Linear regression analysis of sROC generated from mathematical computation of true and false positivity (1-specificity) of each study showed an AUC of 0.81 (95% CI = 0.77-0.84) (Fig. 6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 The most prevalent clinical symptoms are acute respiratory distress syndrome (ARDS) and Interstitial pneumonia. 3 , 4 , 5 , 6 Also, the cardiovascular system has been reported to be frequently affected in COVID‐19 patients, and those with cardiovascular involvement are facing a greater risk of worse outcomes. 7 Atrial fibrillation (AF) is a major etiology for embolism and stroke, particularly if it is not treated with anticoagulative therapy as a preventive stroke measure.…”
Section: Introductionmentioning
confidence: 99%
“…The new coronavirus disease (COVID‐19) pandemic, precipitated by severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2), 1 enormously affecting worldwide communities, has resulted in exceeding 565 million afflicted individuals and over 6 million mortalities as of late July 2022 2 . The most prevalent clinical symptoms are acute respiratory distress syndrome (ARDS) and Interstitial pneumonia 3–6 . Also, the cardiovascular system has been reported to be frequently affected in COVID‐19 patients, and those with cardiovascular involvement are facing a greater risk of worse outcomes 7 .…”
Section: Introductionmentioning
confidence: 99%